LEGAL PROTECTION OF CERTAIN TIME WORKERS IN COMPANIES - Akbar; Marwati Riza; Zulkifli Aspan (Awang Long Law Review, 2023)
This study aims to determine the legal protection of employees for a certain time at companies in Makassar City and the implementation of certain time agreements for companies in Makassar City. Agreement The research method used in the research is the juridical-empirical research method. This research was conducted at PT Dinar Wisesa Mahakarya, Makassar City Manpower Office, and South Sulawesi Manpower Office. The method of data collection is by interview and literature. The results obtained will then be analyzed using qualitative analysis methods. The results of the study show that 1) Specific Time Work (PKWT) at PT. Dinar Wisesa Mahakarya has not fully complied with the regulations in accordance with the applicable laws and regulations. These discrepancies include: first, related to the PKWT extension period which has passed the period stipulated by the labor law. 2) Regarding the nature of the work given to employees/workers with PKWT status at PT. Dinar Wisesa Mahakarya is not in accordance with the type and nature of work regulated in UUTK. At this time the form of legal protection for workers with PKWT status at PT. Dinar Wisesa Mahakarya, including the fulfillment of wages which are above the Makassar City UMR, protection for social security in the form of Health PT. BPJS.